تحليل التدريبات لمادة التعبير التحريري على أساس مهارات التفكير لدى طالبات قسم الإعداد اللغوي في جامعة الراية سوكابومي - Siti Mufarokah; Akhmad Muzakki; Dewi Chamidah (Hasanuddin University, 2023)
One of the most important parts of the textbook is the exercises, as their quality is reflected in the quality of the textbook. This study aims to describe the forms of exercises for the subject of writing skill in the book Al-‘Arabiyah Baina Yadaik for the third book, volume one, and to describe the suitability of these exercises for the basis of thinking skills. This study follows the descriptive approach with a qualitative approach. As a result, the exercises for the subject of writing skill in the Al-‘Arabiyah Baina Yadaik for the third book, the first volume contained five types; (1) writing the topic with a title, (2) writing dramatization in the form of the text, (3) writing the story, (4) writing the summary, (5) writing the part, and that the exercises in it did not include the three thinking skills, as it revolved between re-reading and then writing the summary. The conclusion of the study is that the exercises in the Al-‘Arabiyah Baina Yadaik for the third book, the first volume and for the subject of writing skill, did not have many form. Keywords: Analysis of exercises; Al-‘Arabiyah Baina Yadaik; Ar-Raayah University.